Analysis of the Chinese Airline Network as multi-layer networks. (May 2016) - Du, Wen-Bo; Zhou, Xing-Lian; Lordan, Oriol; Wang, Zhen; Zhao, Chen; Zhu, Yan-Bo
Highlights: The Chinese Airline Network is modelled as multi-layer networks via the k -core decomposition. The network is divided into three layers: Core layer, Bridge layer and Periphery layer. Chinese Airline Network is less redundant than the Worldwide Airline Network. Abstract: This paper encapsulates the Chinese Airline Network (CAN) into multi-layer infrastructures via the " k -core decomposition" method. The network is divided into three layers: Core layer, containing airports of provincial capital cities, is densely connected and sustains most flight flow; Bridge layer, consisting of airports in Tier 2 and Tier 3 cities, mainly connects two other layers; and Periphery layer, comprising airports of remote areas, sustains little flight flow. Moreover, it is unveiled that CAN stays the most robust when low-degree nodes or high flight flow links are removed, which is similar to the Worldwide Airline Network (WAN), albeit less redundant.